2011
DOI: 10.1007/s10388-011-0274-8
|View full text |Cite
|
Sign up to set email alerts
|

Stapled resection for bronchogenic cyst of the esophagus performed using video-assisted thoracic surgery

Abstract: Esophageal bronchogenic cyst is a rare congenital malformation. Although thoracoscopic resection is useful, it has not been adopted for esophageal cysts with a large size or severe inflammatory adhesions. We first reported a case of esophageal bronchogenic cyst that was completely resected using endo-staplers during videoassisted thoracoscopic surgery. A 28-year-old man was referred for the treatment of a mediastinal cystic tumor located between the trachea and esophagus. His chief complaints were coughing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Swanson et al [2] reported a case that had a fibrous stalk between the cyst and the abdominal esophageal wall. Similar to their report, we previously experienced a similar case in which a thin stalk was present between the esophageal bronchogenic cyst and the thoracic esophageal wall [12].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Swanson et al [2] reported a case that had a fibrous stalk between the cyst and the abdominal esophageal wall. Similar to their report, we previously experienced a similar case in which a thin stalk was present between the esophageal bronchogenic cyst and the thoracic esophageal wall [12].…”
Section: Discussionsupporting
confidence: 62%
“…Whereas bronchogenic cysts are lined with pseudostratified ciliated columnar or cuboidal epithelia that sit on a smooth muscle layer and must contain cartilage or bronchial mucous glands, duplication cysts do not contain cartilage or respiratory glands and are lined with two smooth muscle layers [8,9]. Some previous reports have described the presence of elevated levels of tumor marker such as CA19-9 and CA125, and positive staining with a monoclonal antibody against CA19-9 in the esophageal bronchogenic cyst [10][11][12]. Our patient had neither positive immunohistochemical staining for CA19-9 nor an elevated serum CA19-9 level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the last two decades, thoracoscopic surgery has attracted much attention as a less invasive approach for the treatment for benign and malignant diseases [13][14][15]. In 1992, Cuschieri et al [16] first reported performing thoracoscopic minimally invasive esophagectomy (MIE) for esophageal cancer, which sparked the interest of many surgeons because MIE has the potential to lower the morbidity associated with resection and to enable a quicker return to normal function.…”
Section: Introductionmentioning
confidence: 99%